New data on knowledge and application of Information Literacy Framework in higher education libraries - Sanches, Tatiana (2019)
This communication reveals data concerning the knowledge and practices of librarians from Portugal on the ACRL Framework on Information Literacy for Higher Education. The study is supported by a literature review on information literacy crossed with the concept of innovation in higher education libraries’. The data are obtained by analysing the results of a questionnaire sent to Portuguese librarians, regarding their knowledge and application of the Framework. Statistical methods and quantitative data were used to describe the librarian’s attitudes towards new pedagogical practices involving information literacy. The results show that, based on the Framework, the didactic process can be renewed, constituting itself as a schedule of change and innovation.